Understanding The Story of Dzul-Qarnain in QS. Al-Kahfi through The Semiotic Paradigm - Mukhlis, Abdul; Seman, Muhammad bin; Safar, Ahmad Arifin bin (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
This study aims to find the relationship between the meaning of signs and the optimal meaning of the story of Dzul-Qarnain in the Qur'an, Surah al-Kahfi. Through these semiotic signs, it is hoped will make it easier for readers to understand the story of the character Dzul-Qarnain completely, deeply and to know the symbolic message behind the story. To analyze the data, a semiotic method is needed. This study will use the semiotic theory of Charles Sanders Peirce, where a sign is something that represents something in some way or capacity for someone. Something that is used as a sign has a function, Peirce called it ground. The consequences of a sign (representamen) are always in a triadic relationship, namely a sign, object and interpretant. With the semiotic theory of Charles Sanders Peirce, a number of semiotic phenomena in the story of the character Dzul-Qarnain will be seen in more detail so that the reading is more accurate. Apart from that, two interpretations can be achieved, namely the semiotic interpretation of the linguistic signs in the story of Dzul-Qarnain and the semiotic interpretation of the preaching message which is the main goal of the Qur'an in this story.